A practical approach to obesity prevention: Healthy home habits. Issue 11 (27th November 2021) - Fruh, Sharon; Williams, Susan; Hayes, Katey; Hauff, Caitlyn; Hudson, Geoffrey M.; Sittig, Scott; Graves, Rebecca J.; Hall, Heather; Barinas, Jennifer
ABSTRACT: Families have the potential to foster a healthy home environment aimed at reducing the risk of overweight and obesity. Establishing habits associated with reduced risk of obesity and overweight early in childhood can have lasting effects into adulthood. Nurse practitioners can encourage families to participate in healthy habits by addressing areas of growth for obesity prevention within the home. A review of the most recent literature, approximately over the past decade, was used to provide a consolidated source of reference for healthy home habits for the nurse practitioner. The search included terms such as "obesity, " "overweight, " "healthy habits, " "physical activity, " "obesogenic behaviors, " "family meals, " "screen time, " "depression, " "sugary beverages, " and "portion sizes." The information was synthesized into three content areas: nutrition and consumption, patterns of activity, and stress within the home. Establishing healthy habits early in life can protect against the development of overweight and obesity. Nurse practitioners can serve a vital role in the prevention of pediatric, adolescent, and adult obesity. Equipped with the unique role of assisting those from a diverse patient base, nurse practitioners can inform patients how to improve healthy habits to decrease the likelihood of obesity or overweight. Encouraging behavior change related to the healthy habits associated with the prevention of overweight and obesity can have a long-term impact on the health of an entire family.